Real-time learning : how the best companies and leaders make it happen - Johnson, Lauren Keller (2005)
Shows how experiential learning is crucial to an organisation's success. Suggests that the most effective approaches to experiential learning - the ones that advance people through companies - are shaped as much by individuals as by organisations.\n